Approaches to Educating Patients and Their Families About General Anaesthesia and Their Impact on Reducing Perioperative Stress - Kosikowska, Aleksandra; Tołkacz, Aleksandra; Król, Adrianna; Gewald, Maja; Kwiatkowska, Aleksandra (Journal of Education, Health and Sport, 2026)
Introduction: Preoperative anxiety associated with general anesthesia is a frequent and clinically significant problem linked to a poorer perioperative experience, increased distress, and less favorable recovery outcomes. Limited knowledge about anesthesia and the anesthesiologist’s role may increase patient stress. Aim: To examine the literature on educational strategies for patients receiving general anesthesia and, when applicable, their families, with emphasis on their effectiveness in decreasing anxiety and stress, improving knowledge, and enhancing satisfaction. Methods: A narrative review of 28 full-text English-language articles published from 2020 to 2026 was performed using PubMed, Scopus, Web of Science, and Google Scholar. The review covered studies concerning preoperative education, family-oriented interventions, anxiety reduction, and perioperative experience in adult and pediatric populations. Results: Educational interventions, especially multimodal, video-based, multimedia, and virtual reality methods, were linked to lower anxiety, greater preparedness, improved understanding of anesthesia, and increased satisfaction. In pediatric settings, family-oriented strategies were particularly relevant, as parental anxiety strongly affected children’s emotional responses. Verbal counseling remained essential, but combined and technology-assisted approaches seemed to be the most effective. Conclusion: Preoperative education should be considered an integral part of perioperative care. Structured, accessible, and individualized educational strategies may decrease stress, improve cooperation, and strengthen the patient and family experience before general anesthesia.